Web based Application Design for Storage of Eucharistic Liturgical tools in St. Peter's Catholic Church Warembungan - Lumintang, Yuek V.R; Rindengan, Yaulie Deo. Y; Poekoel, Vecky C. (Jurnal Teknik Informatika, 2021)
Catholicism is one of the recognized religions in Indonesia. Nowadays, many Catholics do not know their own worship tools. Storage systems have been widely used or developed in a place with various technologies and systems. Some of these things are made to make it easier for users to do their work. One of them is a system that will be created to store, add, delete, or edit data on eucharistic liturgical instruments. Before technology developed as it is today, people often had difficulty in manually collecting data because of the large amount of data provided. The application that will be made uses the RAD method and aims to assist related parties in managing or collecting data on the eucharistic liturgical instruments in the St. Peter warembungan church. This application is made on a website-based basis, with web programming languages, including HTML, CSS, PHP and JavaScript, along with a MySQL database for data storage. The results of the black box method test show the smooth running of the system that is made to run well and also provide convenience for users to find out information from the data of the Eucharistic liturgical instruments at the St. Peter Warembungan church.